Effect of ossicular chain deformity on reverse stimulation considering the overflow characteristics of third windows. Issue 3 (17th February 2022) - Liu, Houguang; Xue, Lin; Yang, Jianhua; Cheng, Gang; Zhou, Lei; Huang, Xinsheng
Abstract: Stimulating the round window membrane via an active actuator of the middle ear implant, named the reverse stimulation, has become an option to help patients with ossicular chain deformity (OCD) to restore hearing. However, there is still no concise description of how OCD affects reverse stimulation considering the overflow characteristics of third windows. In the present study, an impedance model considering the vestibular and cochlear aqueducts was used to investigate the dynamic response of the cochlea to reverse stimulation under OCD. First, a finite-element (FE) model of the middle ear and the ear canal was used to estimate the changes in reverse middle-ear impedance caused by ossicular chain fixation and ossicular chain interruption. Then, the impedance model was used to predict the reverse transfer function, which characterizes the effect of OCD on the dynamic response of the cochlea. The results show that ossicular chain fixation reduces the reverse stimulation's performance. Moreover, the existence of the third windows complicates the effect of ossicular chain fixation on the reverse stimulation and boosts obviously the reverse stimulation's performance at low frequencies. In contrast, regardless of the existence of third windows, ossicular chain interruption enhances the effect of reverse stimulation.